A clinico-epidemiological and investigative study of post adolescent acne - Sharma, Nidhi; Raina, Garvit (International Journal of Research in Dermatology, 2024)
Background: Although acne is usually recognized as an adolescent skin disorder, the prevalence of adults with acne is increasing. The clinical and epidemiological data of adult acne were evaluated with a view to establishing possible contributing etiological factors and observing whether clinical features differ from adolescent acne. Methods: A total of 170 patients over the age of 25 years with acne were taken up for the study and a detailed history and clinical examination was done. Hormonal profile was done in all the patients. The data was statistically evaluated and inferences drawn. Results: Out of 170 patients included in the study 87.6% were women. The mean age of the patients was 33.5 years. Persistent acne was observed in 62.4%, while it was late onset in 37.6%. Most common predominant site of involvement was cheek (78%), followed by chin (62%), and mandibular area (33.2%). Family history of acne was present in 15.3%. Premenstrual flare was seen in 31.2% of female patients, obesity in 25.9%, hirsutism in 41.8% and menstrual abnormalities in 15.1%, but raised laboratory markers of hyperandrogenism were observed in only 4.02%. Conclusions: The study identified key contributing factors and patterns of post adolescent acne, providing valuable insights for tailored management strategies.